Development of a proxy-free objective assessment tool of instrumental activities of daily living in mild cognitive impairment using smart home technologies - Jekel, Katrin; Frölich, Lutz (Journal of Alzheimer's disease, 2016)
Background: The assessment of activities of daily living (ADL) is essential for dementia diagnostics. Even in mild cognitive impairment (MCI), subtle deficits in instrumental ADL (IADL) may occur and signal a higher risk of conversion to dementia. Th
Gesehen am 07.02.2019